The Influence of Capital Structure and Governance on Financial Performance - Fahmi, Darul; Sawukir, Sawukir (Jurnal Multidisiplin Sahombu, 2025)
This study examines the influence of capital structure (Debt-to-Equity Ratio/DER) and corporate governance (independent commissioners) on financial performance, measured by Return on Assets (ROA). Using multiple linear regression analysis on companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023, the findings reveal that independent commissioners have a significant positive impact on ROA, while capital structure does not significantly influence profitability. The R Square value of 41.5% indicates that capital structure and corporate governance explain only part of ROA variations, with the remaining 58.5% influenced by other factors. These results highlight the importance of strong governance in enhancing financial performance and suggest that companies should focus on transparent and accountable management practices to achieve sustainable growth.